The numerical analysis of the acoustic streaming effect of a cavity acoustic black hole - Huang, Meilian; Liang, Xiao; Su, Liang; He, Xingyun; Li, Danni; Chu, Jiaming; Wang, Shengsheng; Liang, Haofeng; Zhang, Yongyan (Frontiers in Materials, 2022)
In this study, we use the numerical methods to study the acoustic streaming effect of Acoustic Black Hole (ABH). Firstly, we build a ABH model to study the acoustic streaming effect. By deriving the waves equations and solving the Navier-Stokes equations, we obtain the flow field, sound field and temperature field under the acoustic excitation. Secondly, by analyzing the result of the simulation, it reveals the mechanism of acoustic streaming effects work on the sound transmission characteristics of cavity ABH. The numerical results show that the abrupt decrease of the sound pressure is caused by the great changes in the velocity gradient which caused by the catastrophe of cross section. And the energy of the sound waves also can be dissipated by the thermal viscous layer at low frequencies. Finally, based on the acoustic streaming effects of the acoustic medium in the ABH, we propose the feasible methods to enhance the sound insulation. Increasing the cross section of the cavity in ABH can get a better sound insulation effect at high frequencies and decreasing the cross section can improve Sound Transmission Loss (STL). Through the optimization, the STL can reach more than 25dB at low frequencies.